Choline Acetyltransferase (ChAT) Immunoreactive Structures in the Porcine Extrahepatic Bile Ducts - Stefanov, Ivaylo; Hrischev, Petar (Acta Scientiae Veterinariae, 2024)
Background: In the domestic pig, mast cells, neural and non-neuronal cholinergic systems in the gallbladder and extrahepatic bile ducts need a detailed morphological study to identify the type and localization of their structural components. The aim of the current study was to quantitatively analyze biliary cholinergic ganglia and nerves as well as non-neuronal cholinergic cells. Materials, Methods & Results: In the present study were used tissue samples from the extrahepatic bile ducts and gallbladders of male clinically healthy pigs. A part of the serial histological sections was stained with hematoxylin and eosin to rule out the presence of pathological findings. Another part of the sections was processed immunohistochemically to determine the expression of choline acetyltransferase and tryptase. Two primary antibodies were used: a polyclonal rabbit choline acetyltransferase and a monoclonal mouse antihuman mast cell tryptase. The number and dimensions of cholinergic ganglia, perikaryons and nerves forming ganglionic nerve plexuses in the propria, muscular and subserosal layers were estimated. The immunoexpression of choline acetyltransferase in biliary glandular cells and mast cells was also detected and analyzed. Discussion: The current study provided original information on the number and dimensions of intramural choline acetyltransferase positive nerves, ganglia, and perikaryons of ganglion neurons, showing that ganglia in porcine gallbladder and extrahepatic bile ducts are cholinergic. It was revealed that the localization of intramural nerves and ganglia in the porcine gallbladder and extrahepatic bile ducts was similar to that in man. The expression of choline acetyltransferase found by us for the 1st time in the mast cells of porcine gallbladder and extrahepatic bile ducts suggests, on the one hand, the possibility of its synthesis and release from these cells, and on the other hand, its involvement in modulating the interaction between mast cell and intramural neurons in the studied organs. Interactions between mast cells and neurons may potentially contribute to the pathogenesis of many diseases in gastrointestinal tract. Keywords: mast cells, ganglia, choline acetyltransferase, tryptase, bile ducts, pigs.